A Placebo-Controlled, Multiple Ascending Dose Study to Evaluate the Safety, Pharmacokinetics and Pharmacodynamics of Avagacestat (BMS-708163) in Healthy Young and Elderly Subjects - Dockens, Randy; Wang, Jun-Sheng; Castaneda, Lorna; Sverdlov, Oleksandr; Huang, Shu-Pang; Slemmon, Randy; Gu, Huidong; Wong, Oi; Li, Hewei; Berman, Robert M.; Smith, Christina; Albright, Charles F.; et al. (Clinical pharmacokinetics, 2012)
Background and Objectives Avagacestat is an orally active γ-secretase inhibitor that selectively inhibits amyloid β (Aβ) synthesis in cell culture and animal models. The objective of the current study was to assess the pharmacokinetics, pharmacodynamics, safety and tolerability of multiple doses of avagacestat over 28 days in healthy young men and elderly men and women in a placebo-controlled, sequential-panel, ascending multiple-dose study. Methods Thirty-three young men were assigned to four serial dose groups of avagacestat 15, 50, 100 or 150 mg (n = 6–7 per dose), or placebo (n = 2 per dose panel; 8 subjects total) once daily for 28 days. Elderly men and women were assigned to serial dose groups of avagacestat 50 mg and then 100 mg (n = 7 men, 6 women) or placebo (n = 2 men, 2 women) once daily for 14 days per dose level. Results Avagacestat was rapidly absorbed, had a terminal elimination half-life of 38–65 h, and reached a steady-state concentration by day 10 of daily dosing. Exposure in young subjects increased in proportion to dose. There were no apparent differences in steady-state area under the plasma concentration–time curve between young and elderly subjects; however, elderly subjects demonstrated a higher maximum plasma concentration for avagacestat. Doses of avagacestat >50 mg/day reduced steady-state trough concentrations of CSF Aβ 1–38 , Aβ 1–40 and Aβ 1–42 in a dose-dependent fashion over 28 days of daily dosing. There were no signs of potential Notch-related dose-limiting toxicities. Conclusion The results support continued evaluation of avagacestat in an elderly target population with predementia and mild to moderate Alzheimer’s disease.